2015
DOI: 10.1002/cbf.3122
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin modulates keratoconus metabolism in vitro

Abstract: Corneal scarring is the result of a disease, infection or injury. The resulting scars cause significant loss of vision or even blindness. To-date, the most successful treatment is corneal transplantation, but it does not come without side effects. One of the corneal dystrophies that are correlated with corneal scarring is keratoconus (KC). The onset of the disease is still unknown; however, altered cellular metabolism has been linked to promoting the fibrotic phenotype and therefore scarring. We have previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…It has previously been reported that DHEA inhibits the PPP in human endometrial stromal cells 49 and tumor cells 50 . The PPP pathway has also been identified by us as a target of the antioxidant, Quercetin, in HKCs with upregulation of glucose-6-phosphate, glyceraldehyde-3-phosphate, and erythrose-4-phosphate 51 . Treatment of HCFs and HKCs with 2.5 ng/mL and 5 ng/mL DHEA did not cause a significant reduction in PPP intermediates in our model ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…It has previously been reported that DHEA inhibits the PPP in human endometrial stromal cells 49 and tumor cells 50 . The PPP pathway has also been identified by us as a target of the antioxidant, Quercetin, in HKCs with upregulation of glucose-6-phosphate, glyceraldehyde-3-phosphate, and erythrose-4-phosphate 51 . Treatment of HCFs and HKCs with 2.5 ng/mL and 5 ng/mL DHEA did not cause a significant reduction in PPP intermediates in our model ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The antioxidant quercetin is a potential therapy that may address both the elimination of oxidants as well as regulation of metabolism in corneas with KC, considering that excessive lactate production has been associated with oxidative stress and KC. [525354] Future studies should focus on therapeutic agents that can bring the ROS/RNS balance into equilibrium and reduce oxidative damage in corneas with KC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the antioxidant riboflavin upregulates the expression of antioxidant compounds in KC stromal cells, downregulates the expression of oxidase genes, and reduces ROS levels in KC ( 18 ). Quercetin may be used to reduce oxidative stress regulatory signals involved in the pathogenesis of KC ( 40 , 41 ). These antioxidative stress drugs may have potential in the clinical prevention and treatment of KC.…”
Section: Discussionmentioning
confidence: 99%